Posmodernidad y Obra de Arte: De Heidegger a Vattimo - Hernández, Biviana (Revista de Filosofía, 2009)
This essay deals with the debate concerning postmodernity in the light of Heidegger’s conception of art and esthetic experience as the putting into effect of truth, and of the theories of Frederic Jameson and Gianni Vattimo regarding the cultural characteristics embraced by the postmodern subject. These agree with the characteristics of works of art insomuch as the esthetic allows the surge of its signifi cant thanks to the influence and role played in its determination by the massive media of communication.